Carboxymethylation of Sago Starch and Sago Waste and the Formation of Carboxymethyl Starchhydrogel Via Irradiation Technique - Zainuddin, Norhazlin (2003)
Carboxymethyl starch (CMS) and carboxymethyl sago waste (CMSW) were synthesized in completely heterogeneous conditions as a product of the reaction of sago starch or sago waste and sodium monochloroacetate (CICH₂COONa) in isopropanol and sodium hydroxide (NaOH). The influence of various parameters on the degree of substitution (DS) was determined. The optimum conditions obtained for CMS were as follows: NaOH concentration, 20% w/v; reaction time, 1 h; reaction temperature, 55°C; and amount of CICH₂COONa, 1.5 mole. Meanwhile the optimum conditions for carboxymethylation of sago waste were as follows: NaOH concentration, 25 % w/v; reaction time, 2 h; reaction temperature, 55°C; and amount of CICI-bCOONa, 2.0 mole. The DS and reaction efficiency (RE) under optimum conditions for CMS were 1.05 and· 85.9%, respectively, whereas for CMSW were 1.04 and 79.5%, respectively.